AI and Writing Skills: Students' Attitudes towards Using AI to Enhance their Writing Based on the Example of Algebra University Students - Martina Stadnik; Ana Lokas Ćošković; Tihana Banko; Domagoj Ružak (Interdisciplinary Description of Complex Systems)
The advent of publicly available AI in the last years has resulted in a major paradigm shift. Its use is starting to pervade most fields and aspects of life – including the world of academia. This article explores how Algebra University students use AI for writing and their attitudes towards this use. The research was done in two parts. The first part comprised one of the students’ required writing assignments. The students were encouraged to use AI, but with a caveat that the final version may not be more than 35% AI-generated. The second part of the research was a short anonymous questionnaire. The aim was to determine whether the students think that AI tools embetter their writing in terms of both language proficiency – a point of particular interest as most of the students are non-native speakers of English – and creativity. The article presents an analysis of the students’ responses and supporting findings of other papers on AI’s role in writing. While the results indicate that students believe AI to be helpful in general and that it enhances their writing skills, its role in and impact on creative writing still remain unclear and require further research into this complex topic.